Implementation of ISO 31000:2018 Framework in Risk Management Analysis of e-Poin Application - Putri, Nandini Nurmalita; Rudianto, Christ (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The e-Poin application is a platform developed by Satya Wacana Christian University to facilitate the submission of activity proposals and financial accountability reports. This application is utilized by work units and student organizations responsible for carrying out activities annually. Ensuring the smooth implementation of this application is crucial, as it directly impacts processes ranging from proposal validation to fund disbursement. Therefore, risk management for the e-Poin application using the ISO 31000:2018 framework is essential to minimize potential risks that could threaten its performance. The research identified 15 potential risks, comprising 13 risks categorized as medium-level and 2 risks categorized as low-level.